Farmers’ perceptions of crop pest severity in Nigeria are associated with landscape, agronomic and socio-economic factors - Zhang, Wei; Kato, Edward; Bianchi, Felix J.J.A.; Bhandary, Prapti; Gort, Gerrit; Werf, Wopke van der (Elsevier, 2018)
Insect pests are a major cause of crop yield losses around the world and pest management plays a critical role in providing food security and farming income. This study links Nigerian farmers’ perceptions of pest severity to the landscape, agronomic, biophysical, and socio-economic context in which agricultural production takes place. A farm household survey was conducted during 2012–2013, collecting data on household characteristics, cropping systems, pest severity and pest management from 805 households in 12 states of Nigeria. Village characteristics and land use information were collected from an accompanying semi-structured village survey. Reported pest severity was negatively associated with the proportions of forest and unused land at the landscape scale. This finding suggests the existence of pest suppressive effects of a diverse landscape under African smallholder agriculture settings, confirming findings of more industrial and larger scale agroecosystems in the temperate zone. Application of fertilizers (chemical and manure) was negatively related to reported pest severity. Moreover, reported pest severity was lower in mixed-cropping systems than in mono-cropping systems, reinforcing the idea of a pest suppression benefit of diverse cropping systems. In conclusion, our findings suggest that the presence of non-crop areas in the landscape and the diversification of agroecosystems may be a viable strategy for smallholder farmers to manage pests with limited reliance of chemical insecticides in Nigeria, but that actual pest management decisions are influenced by a wide range of context-specific factors. The paper adds new evidence on the relationship between different production situation characteristics and pest severity for Nigeria, based on which policy implications are discussed.